PRAKTEK PEMBUATAN DAN SIMULASI ROBOT LINE FOLLOWER UNTUK MENINGKATKAN MINAT BELAJAR SISWA BIDANG IPA DI RUMAH PADA SMPN 6 SELUMA - Afrizal Mayub; M Luthfi Firdaus; Henny Johan (Politeknik Negeri Sriwijaya, 2021)
Community Service is an activity that must be carried out by every Lecturer, therefore Lecturers for S2 Natural Science FKIP Bengkulu University collaborated with the Science Subject Teacher Conference (MGMT) of Seluma District Middle School / MTs dated 24 May 2019 for Community Service activities at SMPN 6. Collaboration It was followed up with community service activities at SMP N 6 Seluma with the title